Clinical Profile of Thalassemia Syndrome in Children of Northern Bangladesh (TAJ: Journal of Teachers Association, 2019)
Background: Thalassemia is a common hematological disorder in our country having wide spectrum of clinical presentation. The frequency and severity of the several types of thalassemia depend on the racial background of the population. Hb-E Beta thalassemia is prevalent in our country.Objective: To see the clinical features of different types of Thalassemia in northern area of Bangladesh. Methods: Hundred cases were selected from Thalassemia patient admitted in department of pediatrics, on May 2012 to October 2012. A prescribed questionnaire was used to record the information. The methods were explained to the patients and consent was taken. Necessary physical examination was performed and investigations were done. The data was analyzed by standard procedure.Results: Out of hundred (100) cases, most (61%) were Hb-E beta Thalassemia, less common (1%) was Hb-E disease, and 1 % case was Hb-E trait. Majority (64%) manifested clinically under one year of age. 54% were male and 46% were female. The major presenting symptom was progressive pallor in 70% cases. Others presenting complaints were low grade fever (40%). Hemoglobin concentration at the time of diagnosis was below 5 gm/dl in 53.33% patients. In hemoglobin electrophoresis it was Hb-E ranged from 54.64 ± 13.02%, Hb-F 34.84±13.73%, Hb-A 23.32± 18.15% and Hb-A2 3.5± 70%. Radiological findings revealed gross bony changes occur in long standing cases. Enlarged cardiac shadow was found in those cases having severe anemia with heart failure.Conclusion: In countries with a high incidence of thalassemia, it is vitally important to offer prospective genetic counseling and to warn carriers about the risks of intramarriage. Nutritional and folic acid supplementation with regular blood transfusion along with iron chelation therapy is essential to improve the prognosis.TAJ 2018; 31(2): 6-11